2020
DOI: 10.1292/jvms.19-0621
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of foreign bodies swallowing syndrome in camels (<i>Camelus dromedarius</i>) with special reference to the role of mineral deficiency

Abstract: This study describes the clinical presentation of ruminal and reticular foreign body syndrome (RRFBS), and evaluates the effect of mineral deficiency on its occurrence in dromedary camels. Thirty dromedary camels were divided into two groups. Group 1 (control) included 10 apparently healthy she-camels. Group 2 consisted of twenty dromedary camels diagnosed with RRFBS on the basis of clinical, ultrasonographic, hematological, and biochemical examinations. Clinical findings showed decreased appetite and milk yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The study showed the plastic bags had been the most prevalent foreign body type which supported by findings of (Mushonga et al, 2015;Sadan et al, 2020;Anwar et al, 2010), this may be due to the presence of plastic bags compared to other causes of foreign bodies bearing in mind the increased usage of plastic bags by humans and the absence of popper collection of the and absence of clear recycling policies.…”
Section: Occurrence Of Foreign Bodies According To Their Nature (Type)supporting
confidence: 58%
See 3 more Smart Citations
“…The study showed the plastic bags had been the most prevalent foreign body type which supported by findings of (Mushonga et al, 2015;Sadan et al, 2020;Anwar et al, 2010), this may be due to the presence of plastic bags compared to other causes of foreign bodies bearing in mind the increased usage of plastic bags by humans and the absence of popper collection of the and absence of clear recycling policies.…”
Section: Occurrence Of Foreign Bodies According To Their Nature (Type)supporting
confidence: 58%
“…Trace element deficiency would possibly play an essential role in the incidence of foreign body ingestion syndrome in dromedary camels (Sadan et al, 2020). Foreign body ingestion syndrome has been related to nutritional deficiency and imbalances in animal nutrients, especially minerals and trace elements such as copper, iron, cobalt, and manganese in addition to selenium (Braun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cobalt supplementation in bolus form could improve the plasma Co status of camels [ 115 ]. A significant difference in cobalt blood status was observed between health camels and those affected by foreign bodies, at 30 ± 1.7 vs. 24.3 ± 2.0 µg/100 mL [ 148 ]. The blood cobalt also decreased in camels affected by anemia [ 96 ].…”
Section: Trace Mineral Status In Camel Bloodmentioning
confidence: 99%